Multiphase modelling of tissue growth in dynamic culture conditions - O'Dea, Reuben (2008)
In this thesis, a series of mathematical models suitable for describing biological tissue growth are developed. The motivation for this work is a bioreactor system which provides perfusion and compressive mechanical stimulation to a cell-seeded scaffold; however, the formulation is sufficiently general to be applied to a vast range of tissue engineering applications. Our models are used to investigate the influence of (i) cell-cell and cell-scaffold interactions, and (ii) the mechanical environment, on tissue growth.